The evolution of the metamorphic series in the NW Fujian Province, the NE Cathaysia Block, and the significance in the reconstruction of Precambrian Supercontinents - Zeng, Wen (Curtin University, 2010)
This thesis focuses on the Paleoproterozoic to Late Paleozoic basement evolution of the metamorphic rocks scattered in the NW Fujian Province, the NE Cathaysia Block the southeastern area of South China. Field observation, systematic sampling and petrographic investigation combined with of whole rock geochemistry, zircon U-Pb, Lu-Hf isotopes, trace elements, amphibole and biotite 40Ar/39Ar analyses and mineral chemistry study were applied in this project to determine the nature, ages and relations of the leucosomes, felsic paragneiss and mafic metamorphic rocks in study area and their implications to the reconstruction of the Precambrian Rodina Supercontinent.Following conclusions are made: 1. Based on this study, according to their metamorphism and deformation characteristics, the metamorphic rock series in the study area can be divided into two types, moderately to strongly metamorphosed rock series that experienced ductile deformation and moderately metamorphosed rock series that have experienced ductile deformations. New La-ICPMS U-Pb zircon ages presented here and in previous study suggest that the original lithostratigraphy should be abandoned and the terminology “Complex” should be used instead of “Group” and “Formation” for the high grade metamorphic rock series in northwestern Fujian, where the protoliths were strongly reworked by Early Paleozoic tectono-thermal events.2. Obvious zircon U-Pb age peaks of ~1800 Ma suggest that the protoliths ofthe Cathaysia Block be comparable to the basements of North America ratherthan those of Eastern India and East Antarctica. Although the peaks of ~1800Ma are also present in Western Australia, their 176Hf/177Hf ratios (0.280706 -0.281510) are apparently lower than those of zircons from SW Cathaysia (0.281515 - 0.282098) and from this study (0.281232 - 0.282213, NECathaysia). Besides, detrital zircons in Cathaysia and NW Yangtze indicatesignificant juvenile input during Paleo- to Mesoproterozoic according to thezircon Hf isotopes, which are distinctly different from Western Australia.These evidences suggest that the basement of the Cathaysia share similaritieswith that of North America, lending support for the Rodinia configurationproposed by Li et al. (2008), in which Cathaysia was next to western Laurentia before and during the late Mesoproterozoic assembly of Rodinia.2. Obvious zircon U-Pb age peaks of ~1800 Ma suggest that the protoliths of the Cathaysia Block be comparable to the basements of North America rather than those of Eastern India and East Antarctica. Although the peaks of ~1800 Ma are also present in Western Australia, their 176Hf/177Hf ratios (0.280706 - 0.281510) are apparently lower than those of zircons from SW Cathaysia (0.281515 - 0.282098) and from this study (0.281232 - 0.282213, NE Cathaysia). Besides, detrital zircons in Cathaysia and NW Yangtze indicate significant juvenile input during Paleo- to Mesoproterozoic according to the zircon Hf isotopes, which are distinctly different from Western Australia. These evidences suggest that the basement of the Cathaysia share similarities with that of North America, lending support for the Rodinia configuration proposed by Li et al. (2008), in which Cathaysia was next to western Laurentia before and during the late Mesoproterozoic assembly of Rodinia.3. The protoliths of the felsic paragneiss in the NW Fujian area are immaturesediments, consisting of greywacke, arkose and lithic arenite compositions.The significant input of the paragneiss protolith was dominantly formed byseveral magmatic events during Neoproterozoic (820 ± 6 Ma, 780 ± 6 Ma, 776± 6 Ma, 758 ± 3 Ma, 740 ± 8 Ma and 722 ± 9 Ma), probably deposited notearly than middle Neoproterozoic (~680 Ma). Many metamorphic rockscontain 0.99 - 0.72 Ga detrital magmatic zircons, which are interpreted asreflecting the tectono-thermal events related to the assembly and break-up of the Rodinia supercontinent during the Neoproterozoic.4. In this study, new La-ICPMS U-Pb anatectic zircon data from the NWFujian area suggest that the strong and widespread tectono-thermal eventswere related to the orogeny probably having started during the MiddleCambrian and lasted until the Middle Devonian, consisting of at least threemain episodes (~473 Ma, ~445 Ma, ~423 Ma), with major orogeny events(including syn- to post-orogenic melting) constrained between ~473 Ma and~407 Ma in the NE Cathaysia, and between ~468 Ma and ~415 Ma in the SWCathaysia. The age peaks in the Cathaysia Block (ca. 488, 471, 455, 440 and415 Ma) are within the age range of the Qinling-Tongbai-Dabie orogen during 512 - 406 Ma. This suggests a possible linkage or interaction of the two orogens.5. The duration of the “Caledonian” orogeny in the NW Fujian area was noshorter than ~50 Myr, starting at ~473 Ma (~Early Ordovician) or earlier, andterminating at ~423 Ma (~Middle Silurian) or later. The “Caledonian”orogenic event in the Cathaysia Block was likely due to an intracontinentalcollision rather than the subduction of oceanic crust or arc-continentalcollision. Considering the inhomogeneous cooling paths for the Tianjingping,the Jiaoxi and Mayuan complexes, and different time restraint of thewidespread anatectic and magmatic events occurred in different places, the“Caledonian” tectono-thermal events in the Cathaysia Block might vary between different segments of the orogen.